Kirk-Othmer Encyclopedia of Chemical Technology 2000
DOI: 10.1002/0471238961.2209142511140116.a01
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Acetal Polymers

Abstract: Poly(vinyl acetal) resins are made by the acid‐catalyzed acetalization of poly(vinyl alcohol) with aldehydes. The reaction favors formation of the 1,3‐dioxane ring, which is a characteristic feature of this class of resins. As of this writing (ca 1997), only poly(vinyl butyral) and poly(vinyl formal) are made in sizable commercial quantities. Most poly(vinyl butyral) is plasticized and made into interlayer for vehicle and architectural safety glazing. The primary use for poly(vinyl formal) is as an important c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Perhaps the earliest report of such a process is from Herrmann and Haehnel, who studied poly(vinyl alcohol) and found that it successfully forms acetals with benzaldehyde in the late 1920s. 55 Poly(vinyl acetal)s-especially poly(vinyl butyral)-have since then become a valuable industrial material, with numerous applications including coatings and adhesives 56 ; development of novel poly(vinyl acetal)s-e.g., more sustainable ones-continues to be a subject of modern research. 57,58 Other condensation-type mechanisms-e.g., aldol condensation, lactonization, and anhydride formation-have been explored in the subsequent years.…”
Section: Side-chain Cyclizationmentioning
confidence: 99%
“…Perhaps the earliest report of such a process is from Herrmann and Haehnel, who studied poly(vinyl alcohol) and found that it successfully forms acetals with benzaldehyde in the late 1920s. 55 Poly(vinyl acetal)s-especially poly(vinyl butyral)-have since then become a valuable industrial material, with numerous applications including coatings and adhesives 56 ; development of novel poly(vinyl acetal)s-e.g., more sustainable ones-continues to be a subject of modern research. 57,58 Other condensation-type mechanisms-e.g., aldol condensation, lactonization, and anhydride formation-have been explored in the subsequent years.…”
Section: Side-chain Cyclizationmentioning
confidence: 99%
“…These ultrathin films were prepared by spin-coating onto polydiallyldimethylammonium chloride (PDAC)-functionalized silicon wafers and subsequently delaminated in water. , The method has been established for polystyrene and poly­(methyl methacrylate), as well as for polyvinyl formal (PVF) . PVF is a polymer with excellent stability , and mechanical properties, , which has been used as electrical insulation coatings and as ion-conducting membranes for Li batteries. , With the spin-coating/delamination technique, large-area ultrathin PVF films could be fabricated for thin-film capacitors, organic light-emitting diodes, and organic field effect transistors …”
Section: Introductionmentioning
confidence: 99%
“…For example, the most abundantly created and degraded polymer on earth is cellulose, which harbors half of all organic carbon. Each monomer is connected by an acetal functional group, but this functionality is nearly absent in the commercial polymer repertoire (save for polyoxymethylene and polyvinyl butyral).…”
mentioning
confidence: 99%